The crimes of womanhood : defining femininity in a court of law - Carlson, A. Cheree, 1957- (Book collections on Project MUSE., 2009)
Cultural views of femininity exerted a powerful influence on the courtroom arguments used to defend or condemn notable women on trial in nineteenth-century and early-twentieth-century America. A. Cheree Carlson analyzes the colorful rhetorical strategies employed by lawyers and reporters in the trials of several women of varying historical stature, from the insanity trials of Mary Todd Lincoln and Lizzie Borden's trial for the brutal slaying of her father and stepmother, to lesser-known trials involving insanity, infidelity, murder, abortion, and interracial marriage. Carlson reveals clearly just how narrow was the line that women had to walk, since the same womanly virtues that were expected of them--passivity, frailty, and purity--could be turned against them at any time. --From publisher's description.